Kit learns a lesson : a school story - Tripp, Valerie, 1951-; Rane, Walter; McAliley, Susan (Middleton, WI : Pleasant Co., 2000)
In 1934 Kit finds that she has hard lessons to learn about the Depression both at home, where she is helping her mother run a boarding house while her father looks for a new job, and at school, where a fight spoils the preparations for the Thanksgiving pageant.
"1934."
"American girl."
"Book 2"--Cover.
5.3
3-6
Keywords: Depressions -- 1929 -- Fiction; Schools -- Fiction; Thanksgiving Day -- Fiction; Boardinghouses -- Fiction; Historical fiction; Great Depression, 1929-1939 -- Fiction; School stories; Thanksgiving Day -- Fiction; Hotels and motels -- Fiction; Historical fiction